Product formulas for weight two newforms - Nikdelan, Younes; Movasati, Hossein (Cadernos do IME - Série Matemática, 2020)
For a weight two newform f attached to an elliptic curve E defined over rational numbers we write f=q_n=1^∞ (1-q^n)^g_n, g_nZ and we observe that for some special elliptic curves g_n is an increasing sequence of positive integers.